THE STRATEGIC ROLE OF ISLAMIC RELIGIOUS EDUCATION (PAI) IN COUNTERING RADICAL IDEOLOGIES IN THE DIGITAL AGE - Sapiudin, Sapiudin; Ika, Ika (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The widespread dissemination of radical ideologies through digital media poses a serious threat to the younger generation. Islamic Religious Education (PAI) has strategic potential to shape ideological resilience and religious moderation, yet it needs to be actualized in line with the challenges of the digital era; Purpose of the Study: This study aims to analyze the role of PAI in countering radicalism in the digital world and to formulate strategies for strengthening PAI learning based on digital literacy and values of tolerance; Methods: The research employs a qualitative approach using literature study and content analysis of primary sources (PAI curriculum, education policies) and secondary sources (journals, books, and online radicalism cases). Data were analyzed thematically to identify solution patterns; Results: Findings indicate that PAI is effective as an anti-radicalism bulwark when combining three aspects: (1) strengthening inclusive religious understanding, (2) integrating digital literacy into learning materials, and (3) collaboration between teachers, parents, and digital platforms. Examples of good practices include using social media for moderation campaigns and interactive case-based learning; Conclusions: PAI does not only serve as a means of transmitting religious knowledge but also as a deradicalization instrument in the digital era. Curriculum innovation and enhancing PAI teachers' digital literacy capacity are essential to maximizing this role.